The emergence of the Ayyubids on the scene of political and military events (534هـــ /1139م) - حمودي شيرين; الصارم وفاء; كاسوحة باسل (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The Ayyubids played an important role in political and military life in the history of the Islamic world, as they were able to establish a sprawling state and the unity of Egypt, the Levant and Jizya under it, and they were able to work to end the Crusader presence as an effective force in the East, and their first appearance was during the reign of the Seljuk Sultan Muhammad Bam Malakshah. (497_512 AH / 1104_ 1118 AD) and the rule of Tikrit Citadel located on the Tigris River gave them a fief, then they moved to serve Imad al-Din Zangi in Mosul, and they continued under Nur al-Din Mahmoud, and their effective role in conquering Damascus and annexing it to the state of Nur al-Din Mahmoud, then they implement the orders of their master Nour al-Din Mahmoud to go to Egypt and protect it from the Crusaders and end the Fatimid Caliphate.